Stop the 'Asian tobacco connection' - Abd Razak, Dzulkifli (2005)
ONE of the predictions for the Year of the Rooster is that the benchmark Kuala Lumpur Composite Index (KLCI) will hit a range between 900 and 1,000 points this year. It looks like the Rooster promises a healthy year for the business community, especially the socalled earth industries which include those in agriculture and plantation sector. But this may not be so for Malaysia's largest tobacco company. In a statement last week (NST, Feb 9), it said it expects a decline in the cigarette market which it squarely blamed on the tax imposed during the recent Budget. This contradicts an earlier news report that the company will experience an increase in sales volume by at least one per cent over last year, according to an industry analyst, Moreover, the same company also announced its highest share price increase over the last five months, that is, since September 2004.